The State of Economics, the State of the World - Basu, Kaushik; Rosenblatt, David; Sepulveda, Claudia (Cambridge, Massachesetts, The MIT Press, 2022)
We live in troubled times. Over the past decade, the world economy has been wracked by financial crises, sovereign debt problems, backlash from political conflict and migrant crises, and, recently, a rise in xenophobia and protectionism. These issues raise major questions about the state of the world and also about the ability of economics to take on such challenges. Are these many economic and political crises and flare-ups symptoms of some deeper, underlying issues? Is economics as a discipline failing us at this time of soul searching? These are the questions that many are asking and that prompted the conference at the World Bank on which this book is based. We decided to bring in some of the finest minds in the profession—economists who have shaped modern economics—to ponder the state of the field and the state of the world in a series of papers. The conference consisted of 2 days of deliberation: The papers were presented, a distinguished group of economists commented on the presentations, and a large audience engaged with them in conversation and debate. This book is the outcome of these 2 days of deliberation.